The Parallel Presentation of Two Functional CTL Epitopes Derived from the O and Asia 1 Serotypes of Foot-and-Mouth Disease Virus and Swine SLA-2*HB01: Implications for Universal Vaccine Development - Lei Feng; Yong-Yu Gao; Mingwei Sun; Zi-Bin Li; Qiang Zhang; Jie Yang; Cui Qiao; Hang Jin; Hong-Sheng Feng; Yu-Han Xian; Jianxun Qi; George F. Gao; et al. (Cells, 2022)
Foot-and-mouth disease virus (FMDV) poses a significant threat to the livestock industry. Through their recognition of the conserved epitopes presented by the swine leukocyte antigen (SLA), T cells play a pivotal role in the antiviral immunity of pigs. Herein, based on the peptide binding motif of SLA-2*HB01, from an original SLA-2 allele, a series of functional T-cell epitopes derived from the dominant antigen VP1 of FMDV with high binding capacity to SLA-2 were identified. Two parallel peptides, Hu64 and As64, from the O and Asia I serotypes, respectively, were both crystallized with SLA-2*HB01. Compared to SLA-1 and SLA-3, the SLA-2 structures showed the flexibility of residues in the P4, P6, and P8 positions and in their potential interface with TCR. Notably, the peptides Hu64 and As64 adopted quite similar overall conformation when bound to SLA-2*HB01. Hu64 has two different conformations, a more stable ‘chair’ conformation and an unstable ‘boat’ conformation observed in the two molecules of one asymmetric unit, whereas only a single ‘chair’ conformation was observed for As64. Both Hu64 and As64 could induce similar dominant T-cell activities. Our interdisciplinary study establishes a basis for the in-depth interpretation of the peptide presentation of SLA-I, which can be used toward the development of universal vaccines.